Optical, charge transport and magnetic properties of palladium retrieved from photometric measurements: approaching the quantum mechanics background. (14th March 2019) - Vargas, W E; Clark, N; Muñoz-Rojas, F; Azofeifa, D E; Niklasson, G A
Abstract: A parametric Drude–Lorentz (DL) model is used to describe the spectral variation of the dielectric functions of bulk palladium samples at low and room temperature. In addition to the contribution of conduction electrons, the contribution of holes is also explicitly accounted for in the model. A simulated annealing method is applied to obtain the optimized values of the parameters involved in the model: volume plasma frequency of conduction electrons, high frequency dielectric constant, collision frequency of holes and corresponding relaxation time, and two additional parameters from which the effective mass of holes and collision frequency of conduction electrons are evaluated. Oscillatior strengths, resonance frequencies, and widths entering in the Lorentz contribution to the dielectric function are also optimized. Renormalization of the oscillator strengths requires the introduction of a new parameter in the context of the DL model: the ratio between number density of conduction electrons and number density of metal atoms, whose optimized value fits very well with its evaluation from band structure calculations and from independent measurements. Inclusion of this parameter in the framework allows us to evaluate additional quantities related to the charge-carrier transport: average effective masses, Fermi energies and electronic densities of states at the corresponding Fermi energies, intrinsic electrical resistivity, intrinsic mean free paths, heat capacities, mobilities, as well as paramagnetic and diamagnetic susceptibilities, for both electrons and holes. The optimized resonance frequencies are compared with energy differences between plausible interband transitions, in accordance with reported band structure diagrams and with our own band structure obtained from density functional theory calculations.